A Multirotor Platform Employing a Three-Axis Vertical Articulated Robotic Arm for Aerial Manipulation Tasks - Paul, Hannibal; Ono, Koji; Ladig, Robert; Shimonomura, Kazuhiro (2018 IEEE/ASME International Conference on Advanced Intelligent Mechatronics (AIM), 2018)
We describe the concept, design and implementation of an aerial robot that is able to achieve precise and complex manipulation tasks at elevated altitudes. The aerial robot in this study consists of a hexarotor platform, a top-mounted gripper module and a robotic manipulator mounted at the bottom of the air-frame. The top-mounted gripper is used to grasp a bar-like object located above the air-frame with the intention to bring the system to a stable resting position at high altitudes. During the process of grasping, the translational and rotational movements of the gripper module is autonomously controlled based on visual feedback obtained from the on-board camera. This, in combination with the manual control of the air-frame, helps the operator to easily achieve grasping a targeted object. After fixing the robot-frame to a suitable target, the bottom-mounted manipulator is used to perform diverse manipulation task. The end-effector of the bottom-mounted manipulator is also able to manipulate the work area above the air-frame by reaching through the space of the arms of the multirotor frame. The combination of a bottom-mounted 2 DOF manipulator and a 1 DOF rotation mechanism of the top mounted gripper results in a three-axis vertical articulated manipulator system able to operate at elevated altitudes.